ANALISIS PROFESIONALISME JURNALIS (STUDY PADA SURAT KABAR MEDIA NUSANTARA LAMPUNG) - Yunada Arpan (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2018)
`Human Resources owned by the press need to be developed because of human resources asa determinant of success through the professionalism of journalists. This study aims to identify theinfluence of organizational commitment, organizational climate and interpersonal communicationtogether to the professionalism of Media Nusantara Newspapers journalists. The population of this studyconsisted of 54 Journalists, and all populations were taken as samples.Determination Coefficient is 0.584. It means that organizational commitment, organizational climate andinterpersonal communication affect simultaneously to journalist’s professionalism by 58.4%. Theequation of the regression line is Y = 7,297 + 0,052 X1 + 0,599 X2 + 0,323 X3. Organizationalcommitment has no significant effect on journalist’s professionalism. Interpersonal communicationsignificantly affects journalist's professionalism. Organizational climate variable is the most dominant ininfluencing journalist’s professionalism of Media Nusantara newspaper.